Acute and chronic effect of high-intensity interval training in nutral and hot environment on serum BDNF levels in healthy men - Elnaz Taherirad; Hamid Rajabi (Shahid Beheshti University, 2018)
Purpose: The purpose of this study was to determine the effect of high intensity interval training intemperate and warm environment on serum BDNF in healthy men.Methods: In this research, 24 healthy male students according to vVo2max estimation divided to 3 groups,training in the warm environment (n=8), training in the temperate environment (n=8) and control (n=8)categorized as matched. Subjects of experimental group were trained 12 sessions for two weeks. Each sessionincluded 5 set of 150 seconds running on treadmill with %85-90 of vVo2max with 150 seconds active recoverybetween each set with 50 percent of vVo2max. Serum BDNF was assessed using ELISA kits and the data wereanalyzed by one-way ANOVA.Results: The results show that one session high intensity interval activity in warm (p=0.018) and temperate(p=0.045) environment induce significant increment in serum BDNF, However between training group,significant difference was not observed (p=0.262). Furthermore two weeks of high intensity interval trainingin warm (p=0.001) and temperate (p=0.012) environment resulted in significant increment in serum BDNF,also two weeks of training on the level of BDNF not produce significant difference between training andcontrol groups (p=0.267).Conclusions: It seems that high intensity interval training regardless of whether in temperate or warmenvironment increases the level of BDNF.